Historical Development of the Constitutional Social Rights in the Hungarian Constitutional System in the 20th Century - András Téglási (Journal on European History of Law, 2024)
The paper introduces the emergence, development of the constitutional social rights, and gives a historical overview to these rights in the 20th century. The aim of the paper is to show when the social idea and the appearance of social rights in the constitution began in the Hungarian constitutional system. However, according to the Hungarian legal literature, the first constitutional declaration of social rights in Hungary took place with the adoption of the 1949 constitution (Act XX of 1949), but as a result of my research I will show that in fact social provisions can be found in Article 6 of the so-called final Constitution of the Hungarian Soviet Republic. The paper shows how social provisions appeared in the so-called minor constitution of 1946, and then describes the social law provisions of the socialist constitution of 1949. The paper also shows how the social provisions of the 1949 Hungarian People’s Republic Constitution changed between 1949 and 1989, and then describes in detail the changes in the social provisions of the Hungarian Constitution as a result of the political transition in 1989. The paper concludes with a description of the historical development of social rights in the 1989 constitution of the Hungarian People’s Republic, without going into the new Fundamental Law in force in 2012.